Sustainable Practices for Rice Agripreneurs - Stephanie Kim Ramos; Arly N. Visperas; Clarisse S. Vila; Lurene Myles V. Bernales; Aira Camille J. Cenizan; Jemyma Joyce M. Decenon; Mark Juven C. Sibucao (Future Science / FSH-PH Publications, 2026)
This study,